KRITIK TERHADAP PEMIKIRAN GERAKAN KEAGAMAAN KAUM REVIVALISME ISLAM DI INDONESIA - Zuhdi, M. Nurdin (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Agama Islam Negeri Metro, 2011)
Gerakan revivalisme Islam merupakan gerakan keagamaan yang akhir-akhir ini ramai dibicarakan. Gerakan revivalisme Islam ini mewakili berbagai corak gerakan yang ada selama ini, diantaranya adalah Ikhwanul Muslimin (IM) di Mesir, gerakan Front Pembela Islam (FPI), Hizbut Tahrir Indonesia (HTI), Majelis Mujahidin Indonesia (MMI), Laskar Jihad dan Dakwah Salafi. Gagasan yang ditawarkan oleh gerakan revivalisme Islam ini adalah mengembalikan teks kepada karakter ideologis yang statis, ahistoris, sangat ekslusif, tekstualis dan bias patriarkis. Gerakan ini mendukung penerapan syariat Islam secara keseluruhan dalam sendi kehidupan masyarakat. Sehingga kelemahannya yang muncul adalah produk penafsiran teks eksegetik yang cenderung linier-otomistic dalam menafsirkan teks al-Qur’an dan mengabaikan kontektualisasi teks. Padahal teks (al-Qur’an) haruslah dipahami sesui dengan konteksnya agar teks dapat berbicara. Dengan demikian prinsip al-Qur’an yang shalih li kulli zaman wa makan dapat terbukti. Islamic revival movement is a religious movement which is discussed by many lately. The idea of the revival movement is to restore the text to the ideological character of the static, ahistorical, very exclusive, textualist and patriarchal bias. This article seeks to reveal the thoughts of the Islamic revival movement in Indonesia. The method used in this study is both descriptive-critical analysis by collecting existing data, and then describes and analyzes the critical-analytical approach. This study sought to prove that any product of religious thought is influenced by the background surrounding the birth of a religious movement. Therefore, the product should always be open to ideas and have not to criticize scared, considering he was a relative and construction human nature alterntative. In addition, research is also intended to do a 'criticism' and then look for creative synthesis of the methodologies and typologies that exist on the thinking of the religious movement of Islamic revivalism studied. Synthesis results are expected to be contribution to knowledge in religious thought in the contemporary era, especially in Indonesia. Based on the theoretical framework of a typology of religious thought, through critical approaches-analysis concluded that there are at least four typologies of religious thought in the contemporary era, namely: quasi-objectivist typologies traditionalist, revivalist quasi-objectivist, subjectivist and typology typhology quasi-modernist objectivist. This revival movements embracing quasi-objectivist revivalist typology is a genuine understanding of the religion. In the sense of a genuine understanding of the religion they are referring to is an understanding of the return of religion to the ideological character of the static, ahistorical, very exclusive, tektualis and patriarchal bias. According to their religion in the present era must be understood according to the age where religion is lowered regardless of the context in the present era. So the weakness that emerges is the product exegetical interpretation of a text which tends to linear- atomistic in interpreting the text of the Qur'an and ignore contextualization text. Though the text (al-Qur'an) must be understood within their context so that text can be explained. Thus the principle of al-Quran compatibility in all times and contexts can be proven.